The Union of South Africa towards the Outbreak of the Second World War - Arkadiusz Żukowski (Ksiegarnia Akademicka Publishing, 2021)
At the outbreak of the Second World War the Union of South Africa was military unprepared and divided politically. The division into supporters and opponents of the war against Germany was clear, both in the Parliament, as well as in South African society, particularly among large parts of the Afrikaners it manifested itself as significant political support and public acceptance of the ideology of Adolf Hitler and the Third Reich. The moderate Afrikaners and first of all the English‑speaking population supported joining the war on the side of the Allies. In the parliament, the issue has led to a government crisis. The Union of South Africa as a British Dominion finally declared war on Nazi Germany. In a relatively short time the state was able to prepare its institutions, society and economy for participation in the war. An important role in the consolidation of the political elite and society in the fight against Nazi Germany on the side of to the Allies was played J.C. Smuts.